Levan based fibrous scaffolds electrospun via co-axial and single-needle techniques for tissue engineering applications - TOKSOY ÖNER, EBRU; GÜNDÜZ, OĞUZHAN (ELSEVIER SCI LTD, 2018)
This represents the first systematic study where levan polysaccharide was used to fabricate fibrous matrices by co-axial and single-needle electrospinning techniques. For this, hydrolyzed (hHL) and sulfated hydrolyzed (ShHL) Halomonas levan were chemically synthesized and used together with polycaprolactone (PCL) and polyethyleneoxide (PEO) for the spinning process. In co-axially spun matrices, ultimate tensile strength (UTS) were found to increase with increasing ShHL concentration and elongation at break of PCL + ShHL matrices increased up to ten-fold when compared to PCL matrices. Similarly, in single-needle spun matrices, higher elongation at break values were obtained by blending HL and ShHL with PEO pointing to the effective energy absorbing features. Dense and fine fibers were characterized by FTIR and SEM. Cell viability and fluorescence imaging of L929 fibroblasts and HUVECs as well as heparin mimetic activity of the matrices pointed to their high potential to be used in decreasing neointimal proliferation and thrombogenicity of grafts and prosthesis.
Keywords: Halomonas levan; Co-axial electrospinning; Scaffolds; FTIR; Anticoagulation; Tissue engineering; HALOMONAS SMYRNENSIS AAD6(T); BIOMEDICAL APPLICATIONS; MULTILAYER FILMS; STENT THROMBOSIS; VASCULAR GRAFT; SULFATED LEVAN; HEPARIN; REGENERATION; NANOFIBERS; EXOPOLYSACCHARIDES